SEMIOTIKA SINTAKTIK PADA DESAIN KEMASAN ENAM VARIAN RASA PRODUK POCKY INDONESIA - Syamira Sungkar; Diah Asmarandani; Krishna Hutama (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2020)
Syntactic Semiotics in the Design of Indonesian Pocky Products with six variants. Snacks are foods that are popular with all people of all ages. Wafers, sweets, biscuits, chips and others are included in the category of snacks. Pocky is a chocolate-coated biscuit stick, from Japan, produced by Ezaki Glico. Pocky products entered Indonesia in 2014 with 6 variants: chocolate, strawberry, matcha, cookies & cream, double choco, and banana. In this study, researchers will examine the design packaging of Indonesian Pocky products using Morris Syntactic Semiotics theory and also packaging design theory. Analyze how the integration, uniformity, and continuity of the six pack packaging design flavors of Indonesian Pocky products. This type of research is a qualitative study with an intrinsic case study, discussing the design of Indonesian Pocky snack food packaging products. The method used in this research is interpretational analysis based on semiotics theory. The results showed that the packaging design of Indonesian Pocky products had cohesiveness, uniformity, and continuity, by analyzed their visual signs using Morris Syntactic Semiotics Theory.